2021
DOI: 10.1620/tjem.255.71
|View full text |Cite
|
Sign up to set email alerts
|

Association between Premenstrual Symptoms and Posttraumatic Stress Symptoms by COVID-19: A Cross-Sectional Study with Japanese High School Students

Abstract: COVID-19 has caused an unprecedented global pandemic. Premenstrual symptoms include mood-related, behavioral, and physical symptoms that are limited to the luteal phase of the menstrual cycle. Psychosocial stress is a risk factor for premenstrual symptoms. The aim of this study was to examine the association between premenstrual symptoms and stress caused by COVID-19. We analyzed data from 871 students with regular menstrual cycles who completed the Premenstrual Symptoms Questionnaire (PSQ), Fear of COVID-19 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Further, there were a highly statistically significant relationships between dysmenorrhea and learning difficulties as well as the interpersonal relationships among students (p<0.001). Our findings was consistent with findings of previous systematic reviews and meta-analyses in low and middle-income countries that concluded that dysmenorrhea has a statistically significant negative effect on academic performance both in school and during higher education [23][24][25][26][27][28].…”
Section: Results and Dissectionssupporting
confidence: 93%
See 1 more Smart Citation
“…Further, there were a highly statistically significant relationships between dysmenorrhea and learning difficulties as well as the interpersonal relationships among students (p<0.001). Our findings was consistent with findings of previous systematic reviews and meta-analyses in low and middle-income countries that concluded that dysmenorrhea has a statistically significant negative effect on academic performance both in school and during higher education [23][24][25][26][27][28].…”
Section: Results and Dissectionssupporting
confidence: 93%
“…These results were consistent with those of the previous studies among women of childbearing age [18][24]. Furthermore, recent studies have reported an increase in menstrual pain and a deterioration in a menstrual pattern during the pandemic [25][26]. In addition, a study from Palestine indicated that students with irregular menstrual cycles were almost twice as likely to have dysmenorrhea [27].…”
Section: Results and Dissectionssupporting
confidence: 92%
“…The results of this study found that the negative impacts of PMS on academic performance were lack of concentration (50%) and work difficulties (42.9%). These findings are consistent with previous research findings that indicated PMS affects female university students and influences their academic performance, social engagement, and their quality of life [25][26][27][28][29]. About (56.5%) of participants had the COVID-19 infection during the pandemic.…”
Section: Resultssupporting
confidence: 92%
“…First of all, the incidence of PMS during the pandemic among 190 female nursing students was 77.9% (23). Whereas in another research done in a Japanese high school, it was discovered that the PSQ (premenstrual syndrome questionnaire score) considerably increased in the PTSS (Posttraumatic Stress) group by (32.8%) during the pandemic compared to data gathered in 2019 before the pandemic, which was (25.4%) and 49 (5.6%) (24).…”
Section: The Impact Of Covid-19 On the Menstrual Cycle And Premenstru...mentioning
confidence: 91%
“…Women with PTSS are younger and have higher menstrual pain (24). Despite this, 46% of women experienced a change in their menstrual cycle since the pandemic began, compared to 25% before the pandemic (25).…”
Section: The Impact Of Covid-19 On the Menstrual Cycle And Premenstru...mentioning
confidence: 99%